2018
DOI: 10.1159/000494995
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Phenotype and Identification of a Novel Candidate Gene for Immunodeficiency in 5q11 Microdeletion Syndrome

Abstract: Array CGH has led to the delineation of innumerable microdeletion syndromes. We present a patient with a 7-Mb deletion at 5q11.2 with previously unreported features, such as immunodeficiency, asymmetry of hands and feet, joint laxity, and agenesis of corpus callosum. The clinical features of this patient are compared with 13 patients reported previously. A common critical region (CCR) of 1.4 Mb (54-55.4 Mb) is defined in all cases including the present one. Of the 14 genes present in CCR, IL6ST is proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…Numbers at bars refer to the DECIPHER identity number. Vertical dotted line indicate the SRO previously suggested by Arora et al (2019) while vertical full blue line shows the SRO suggested by our study…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Numbers at bars refer to the DECIPHER identity number. Vertical dotted line indicate the SRO previously suggested by Arora et al (2019) while vertical full blue line shows the SRO suggested by our study…”
Section: Resultssupporting
confidence: 79%
“…Furthermore, smaller sized deletions are needed to determine whether this new SRO is actual the critical region of 5q11.2 microdeletion syndrome, since it cannot be ruled out that genes outside the new SRO are causative due to the large size of the deletions in the patients used for narrowing the SRO. Finally, a mild-severe learning difficulty and/or ID has so far been identified in 13 out of 14 subjects reported (Arora et al, 2019). Arora et al (Arora et al, 2019) stated that subject 3 described in 2014 (de Jong et al, 2010) did not have a DD.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Developmental Quotient (DQ) was calculated as >85. Brain MRI showed, mild ventricular dilatation without parenchymal loss with Chiari 1 malformation [2].…”
mentioning
confidence: 96%
“…To date, only 13 cases of 5q11.2 microdeletion have been reported [2]. Although no different phenotype has been identified for this microdeletion syndrome, published cases share many common clinical features [3,4].…”
mentioning
confidence: 99%